Competitive advantage of hotels in Jinhua --Combining Institutional and Resource based Views - Wang, Wei (2007)
This research endeavors to address the sustainable competitive advantage issue of Chinese firms from the paradigm combining resource based and institutional views. Both views have been used extensively in the strategy research literature in China, and the integrative perspective has the potential to approach the strategy issues new insight by incorporating the institutional influence on resource. Establishing on extensive RBV, institutional theory literature and especially Oliver(1997)ÃÂÃÂ¢ÃÂÃÂÃÂÃÂ work on the combination of RBV and institutional theory, this paper proposes a variant integrative conceptual framework.